Astrocytic phosphatase and tensin homolog deleted on chromosome 10 regulates neuropathic pain by facilitating 3-hydroxy-3-methylglutaryl-CoA reductase–dependent cholesterol biosynthesis. Issue 12 (13th December 2022) - Fang, Yehong; Cui, Huan; Liu, Fan; Su, Si; Wang, Tao; Yuan, Bo; Xie, Yikuan; Ma, Chao
Abstract : Supplemental Digital Content is Available in the Text. This study highlights the beneficial role of cholesterol biosynthesis mediated by spinal astrocytic phosphatase and tensin homolog deleted on chromosome 10 in the alleviation of neuropathic pain. Abstract: Recent studies have noted the role of the phosphatase and tensin homolog deleted on chromosome 10 (PTEN) in developing neuropathic pain, but the underlying mechanisms are obscure. We found that PTEN was mainly expressed in astrocytes in the rat spinal cord and dramatically downregulated after chronic constriction injury (CCI). Intrathecal injection of a PTEN inhibitor induced pain-related behaviors in naive rats. By contrast, administration of a PTEN protector effectively mitigated CCI-induced pain. Adeno-associated virus–mediated overexpression of astrocytic PTEN in the spinal cord reduced glial activation and neuroinflammation and subsequently alleviated pain-related behaviors. Importantly, astrocyte-specific PTEN knockout ( Pten conditional knockout, Pten CKO) mice showed nociceptive sensitization and glial activation. Proteomic analysis revealed that PTEN overexpression upregulated at least 7 enzymes in the cholesterol biosynthesis pathway and the total cholesterol level in the spinal cord of CCI rats. Furthermore, PTEN directly interacted with enzymes, including 3-hydroxy-3-methylglutaryl-CoA reductase, in the cholesterol biosynthesis pathway. Astrocytic 3-hydroxy-3-methylglutaryl-CoA reductase overexpression alleviated both CCI-induced pain and mechanical allodynia in Pten CKO mice. Finally, cholesterol replenishment attenuated CCI-induced pain and suppressed spinal glial activation. Taken together, these findings imply that spinal astrocytic PTEN plays a beneficial role in CCI-induced pain by regulating cholesterol biosynthesis, and an increased level of PTEN may accelerate cholesterol biosynthesis and reduce glial activation, thereby alleviating neuropathic pain. Recovery of PTEN or cholesterol might be an effective therapeutic strategy for neuropathic pain.